Selective fruit maturation and seedling performance in Acacia caven (Fabaceae) - Torres, Carolina Cecilia (2002)
The tight globose inflorescences of Acacia caren commonly initiate several fruits, but only one or a few reach maturity. In this study, we ask whether natural fruit maturation patterns in this species are related to either fruit, seed, or seedling performance. We compared fruit, seed, and seedling characteristics from inflorescences that initiated several fruits but self-thinned naturally to mature one fruit, with inflorescences in which we chose randomly one immature fruit and removed all the others at an early stage of development. Also, we considered two additional natural treatments: inflorescences that initiated and matured two or more pods and inflorescences that naturally initiated and matured one fruit only. Around half of the fruits aborted in both manipulated inflorescences and inflorescences that initiated one fruit only. Pod size, seed number, and individual seed mass did not differ significantly between hand- and self-thinned inflorescences. Seeds from hand-thinned inflorescences showed, however, a significant decline in germination rate. Seeds from the other two additional natural treatments showed intermediate germination percentages. In addition, seedlings derived from germinated seeds produced by artificially thinned inflorescences also tended to perform poorly based on six quantitative seedling traits and seedling survival. The results indicate that progeny from hand-thinned inflorescences are of lower quality than progeny from inflorescences that underwent natural fruit abortion, supporting the hypothesis that A. caven matures selectively those fruits that contain more vigorous seeds.